2020
DOI: 10.1007/s10900-020-00946-1
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacists’ Willingness to Provide Coronavirus Disease (COVID-19) Services and the Needs to Support COVID-19 Testing, Management, and Prevention

Abstract: The need for increased testing is pivotal in the response to the coronavirus disease (COVID-19) pandemic. Recently, through the Public Readiness and Emergency Preparedness (PREP) Act, pharmacists were given the ability to order and administer COVID-19 tests, giving them a better opportunity to engage in the pandemic response across the nation as well as in Idaho. This survey sought to determine Idaho pharmacists' willingness to provide different COVID-19 related services, assess needed resources to provide suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 4 publications
3
28
0
Order By: Relevance
“…The finding that no pharmacy was providing COVID-19 testing was unsurprising since no approved point-of-care (POC) tests were available at the time of the study. The more interesting finding is that there was significant demand and support for pharmacy-based testing, similar to what studies in the Middle East [44] and the USA [31] have found. In this context, and given the fact that at least three rapid POC tests have since been approved in Kenya [45], there is an urgent need to start developing policies to guide implementation.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The finding that no pharmacy was providing COVID-19 testing was unsurprising since no approved point-of-care (POC) tests were available at the time of the study. The more interesting finding is that there was significant demand and support for pharmacy-based testing, similar to what studies in the Middle East [44] and the USA [31] have found. In this context, and given the fact that at least three rapid POC tests have since been approved in Kenya [45], there is an urgent need to start developing policies to guide implementation.…”
Section: Discussionsupporting
confidence: 76%
“…Our findings clearly show that community pharmacies in Kenya were undertaking potentially impactful activities to support the response to the COVID-19 pandemic. Despite a feeling of disconnection from the government-led national response, providers expressed great readiness and motivation for provision of COVID-19-related services, similar to providers in Qatar [30], the USA [31], and other settings around the world [32]. The services pharmacies in our study were providing are generally similar to those suggested by experts in the field [22,[33][34][35], as well as those being provided in other low-to-middle income countries [36][37][38][39] and in high-income settings [30,40,41].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, pharmacists across the countries have risen to the COVID-19 challenges, responding quickly to play a role in combating this pandemic (8)(9)(10)(11)(12). More and more studies have been focusing on community pharmacists and their preparedness for the COVID-19 pandemic (13), willingness to provide COVID-19 testing (14,15), COVID-19 practices and services (16), and occupational exposure (17).…”
Section: Introductionmentioning
confidence: 99%
“…Similar to the previous study, pharmacists had a high level of willingness in providing support to help with pandemic but had expressed a lower level of readiness to perform specific services. 28 , 29 These results may have been impacted by the COVID-19 pandemic. Public health communities and state and national pharmacy associations should capitalize on this willingness among pharmacists to provide emergency response support by providing mechanisms to enable training in emergency preparedness, participation in emergency response, and establishment of MOUs.…”
Section: Discussionmentioning
confidence: 99%